PERAN PEMERINTAH DAERAH DALAM MENGELOLA PENDAPATAN ASLI DAERAH DARI SEKTOR PARIWISATA BERDASARKAN PERATURAN DAERAH PROVINSI BALI NOMOR 9 TAHUN 2019 TENTANG PAJAK DAERAH - Alya Alifia Vendra, Clarissa (UNES Law Review, 2024)
This study aims to examine the authority of the Bali Provincial Government in managing Local Own-Source Revenue (PAD) from the tourism sector based on Regional Regulation (Perda) Number 9 of 2019 concerning Regional Taxes. This research uses a qualitative descriptive approach by collecting data through literature studies, interviews, and analysis of related documents. The findings show that the regulation grants significant authority to the local government in regulating and collecting taxes from various tourism activities, which greatly contribute to PAD. However, the implementation of this regulation faces several challenges, such as the need for effective coordination between local governments and tourism businesses as well as the enhancement of tax management capacities.